PENGARUH PEMBERIAN BAKTERI Bacillus pumilus PADA RUMEN SAPI SEBAGAI PUPUK TERHADAP PERTUMBUHAN Dunaliela salina - Endang Dewi Masithah; Nova Ariesma; Yudi Cahyoko (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Dunaliella salina is one type of natural food that can be used in the hatchery business. The growth of natural food can be supported with an abundance of macro and micro nutrients. The purpose of this study to is to know pngaruh and best dose that can be used to enhance growth Dunaliella salina with cow rumen difermntasi mnggunakan Bacillus pumilus as organic fertilizer. Design research is Lengkap randomized design (CRD) followed by Duncan's Range Test. Treatment research Dunaliella salina was cultured at 3 different dose treatment, 2sebagai control (without fertilizer walne and rumen fermentation) and with 4 replications.The treatment dose of the bacteria Bacillus pumilus given are A (7.5%), B (10%), C (12.5%) as a control D (Fertilizer Walne) and E (rumen without fermentation). Results study to show that the addition of the bacteria Bacillus pumilus in rumen of cattle, mmbrikan significant effect trhadap Dunaliella salina growth. The addition of the bacteria Bacillus pumilus by 10% to mningkatkan growth of Dunaliella salina kpadatan 875,000 and is the culmination of the third day. Keyword : Dunaliella salina, Cow Rumen, Bacillus pumilus